Evaluation of User Experience in the Information System of the Laboratory at Muhammadiyah Ahmad Dahlan University in Palembang Using a User Experience Questionnaire - Yuliani, Sari; Gunawan, Catur Eri; Fadilah, Evi (The Future of Education Journal, 2026)
Laboratory information systems play a crucial role in supporting academic activities, administration, and research in higher education. The system’s effectiveness largely depends on user experience (UX). This study aims to evaluate UX and identify improvement areas in the Laboratory Information System of Universitas Muhammadiyah Ahmad Dahlan Palembang. The evaluation was conducted using the User Experience Questionnaire (UEQ) involving 348 active respondents. The results indicate an overall positive UX. The Attractiveness, Perspicuity, and Efficiency dimensions scored Excellent, indicating that the system is efficient and easy to use. However, hedonic aspects need improvement; Novelty scored the lowest (1.12, Above Average) and Stimulation 1.63 (Good), indicating a lack of innovation and interactive elements. Recommended improvements focus on adding innovative and interactive features to enhance the overall user experience.